Excellent outcomes of children with short bowel syndrome and intestinal failure associated liver disease (IFALD) at Children's National Health System (CNHS), Washington DC. (July 2018) - Torres, Clarivet; Vahe, Badalyan; Mohan, Parvathi
Abstract : Objective: We report the outcomes of short bowel syndrome (SBS) parenteral nutrition (PN) dependent patients with IFALD enrolled in our intestinal rehabilitation program (IRP). Methods: Over a 10 year period, 124 SBS PN-dependent patients were enrolled, 78 (63%) of them had IFALD, defined as conjugated bilirubin (CB) of >=2mg/dL at enrollment and/or abnormal liver biopsy (stage 2-4 fibrosis). Outcomes included death, transplant, time to be weaned off PN, time to achieve normal CB levels. Independent variables included gender, gestational age, diagnosis, and intestinal length. Platelets, albumin, CB were obtained at the start and end of the study. Results: Seventy-eight patients (51 males) had IFALD; of these, at the time of enrollment in IRP, 11 (14%) had normalized CB but had abnormal liver biopsies at CNHS and 66 (85%) had elevated CB. One patient acquired elevated CB, related to severe comorbidities. Median CB was 7.3 mg/dl (2-32 mg/dL). Thirty-three patients (42%) had liver biopsies, of which 32 (97%) had fibrosis, including 17 (52%) with bridging fibrosis or cirrhosis. Fifty-five patients (70.5%) were premature (GA <36 weeks). Median intestinal length was 44 cm (28/78 patients (36 %) had <35 cm). Median age at enrollment was 3.7 months and median daily caloric requirement by PN was 100%. Of the 67 patients with elevated CB, 66 (98.5%) normalized their bilirubin with medical treatment over an average of 11.6 weeks (st.dev. 9.1), using soy bean intralipid emulsion. Fifty seven (85%) reversed their cholestasis while still receiving PN, 2 patients were transplanted (they had 4 and 10 cm of remaining bowel), 2 patients died (cardiac anomalies and Down Syndrome). Four patients moved to another state after normalizing their CB, decreasing their PN from 100 to 56%. Of the 70 remaining patients 57 were weaned off PN (81.4%) over a median time of 5 months. A subset of 8 (10%) patients with initial platelet count of < 100 x 103/mcl (mean 59) was identified. In this subgroup, mean CB was 18.4mg/dL, and mean aspartate aminotransferase (AST) to platelet ratio index (APRI) was 19.4. Yet, all but one of this group achieved normalization of CB within an average of 15.6 weeks (st.dev =12), and a significant improvement of platelet count at the end of follow-up (p-value < 0.001). Overall survival was 97.4%. Due to low mortality in our cohort, logistic regression controlling for independent variables did not find association between initial bilirubin levels and mortality. Conclusion: We demonstrate superior outcomes among children with IFALD. In spite of high acuity (e.g. significant proportion of extreme short gut patients, initial high dependence on PN), we were able to quickly reduce their PN needs and improve IFALD without relying on fish oil base lipid. As one of the larger and well established IRP in the US, we demonstrate high survival rates of our patients without the need for liver/intestinal transplant. Early referral to IRP is recommended.